Preparation method of sodium-enriched sodium ferric sulfate composite material and sodium storage application of sodium-enriched sodium ferric sulfate composite material
Sodium-rich sodium ferrosulfate Na7Fe5.5(SO4)9 and CNTs composite materials were prepared by a two-step low-energy solid-phase ball milling strategy combined with pyrolysis, which solved the low efficiency and safety risks of preparing sodium ferrosulfate composite materials in the prior art. The problem is that the electrochemical performance of sodium storage and long cycle life are achieved.
Patent Information
- Application Number
- CN202411536171.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The prior art has problems such as dust pollution, low efficiency, high water resource consumption, strict equipment requirements, large energy consumption and safety hazards when preparing sodium ferrosulfate composite materials, and lacks sodium-rich materials.
A two-step low-energy solid-phase ball milling strategy combined with pyrolysis was used to prepare a composite material of sodium-rich sodium ferrosulfate Na7Fe5.5(SO4)9 and carbon nanotubes (CNTs). The uniformity of the material is ensured through specific ball milling and heat treatment steps. Efficiency.
The prepared Na7Fe5.5(SO4)9/CNTs composite material has high uniformity, excellent sodium storage electrochemical properties, good rate performance and stable long cycle life, and is suitable for large-scale production and industrial applications.
Smart Images

Figure CN119390128A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sodium ion batteries and relates to a preparation method of a sodium-enriched sodium iron sulfate composite material and a sodium storage application thereof. Background Art
[0002] Sodium-ion batteries are potential candidates for replacing lithium-ion batteries for large-scale energy storage applications. Polyanionic compounds are one of the four important materials (polyanionic compounds, layered oxides, Prussian blue analogs and organic materials) for electrochemical energy storage and conversion in sodium-ion batteries. Sodium ferric sulfate (NFS) among polyanionic compounds has significant low-cost advantages, a wide source of production raw materials and is green, and is a type of economically efficient and environmentally friendly material. When applied to the positive electrode of sodium-ion batteries, NFS has an operating voltage of up to ~3.8V and a theoretical capacity of 120mAh / g, thus having a significant advantage in high energy density. In addition, NFS has a stable crystal structure and strong resistance to thermal failure during the charge and discharge process, so it has long-cycle application potential and high safety. At the same time, compared with lithium-ion batteries, sodium-ion batteries have strong low-temperature fast charging capabilities and a small capacity decay. Therefore, sodium-ion batteries with NFS as the positive electrode material are more suitable to replace lithium-ion batteries and be used in large-scale energy storage scenarios with low energy density requirements and low cost requirements; they are expected to completely replace lead-acid batteries and be used in two-wheeled and three-wheeled electric vehicles; they can also partially replace lithium-ion batteries and be used in energy storage applications such as four-wheeled low-speed vehicles.
[0003] At present, spray drying, freeze drying, sol-gel and one-step high-energy ball milling technology are the main methods for preparing sodium iron sulfate composite materials. However, spray drying will cause certain dust pollution, freeze drying and sol-gel methods are inefficient; at the same time, the above three methods require a lot of water resources. In order to avoid Fe in NFS precursor, 2+ Oxidation requires the use of a large amount of chelating agents, and the heat treatment process should be additionally kept at about 200°C to remove excess crystal water. The above challenges are not conducive to the large-scale industrial preparation and application of NFS materials in the field of electrochemical energy storage. In contrast, the ball milling process has the advantages of simplicity, high efficiency and high yield. However, one-step high-energy ball milling has strict requirements on equipment, high energy consumption, certain safety hazards and difficulty in synthesizing uniform materials. In addition, the Na-rich composition can supplement a certain amount of Na to the full battery to improve the coulombic efficiency without significantly sacrificing the material's cycle stability, but the NFS material family still lacks Na-rich materials. Therefore, it is still a difficult problem to develop an efficient, inexpensive, high-yield and uniform synthetic strategy to prepare sodium-rich sodium iron sulfate composite materials. Summary of the invention
[0004] In view of the shortcomings of the prior art and the blank of material synthesis, the problem to be solved by the present invention is to provide a method for preparing a sodium iron sulfate composite material, synthesizing sodium-enriched sodium iron sulfate Na7 Fe 5.5 (SO 4 ) 9 Composite materials with carbon nanotubes (CNTs). This method has the advantages of simple process, large output, high efficiency, strong controllability and good repeatability; the prepared Na 7 Fe 5.5 (SO 4 ) 9 / CNTs composite materials not only have good uniformity, but also excellent electrochemical performance for sodium ion storage, and are suitable for large-scale production and industrial applications.
[0005] The technical solution to solve the problem of the present invention is:
[0006] The first aspect of the present invention is to provide a method for preparing a sodium-enriched sodium iron sulfate composite material, using ferrous sulfate, sodium sulfate and carbon nanotubes, through a two-step low-energy solid phase ball milling strategy combined with pyrolysis to prepare Na 7 Fe 5.5 (SO 4 ) 9 / CNTs composite material, the specific steps are as follows:
[0007] Step 1: iron-based sulfate and dispersed CNTs are loaded into a ball mill according to a mass ratio of 6-78:0.4-6, and ethanol or acetone solution is injected. The ball mill is carried out at a low speed of 350-450r / min for 12-24h under the protection of an inert atmosphere. After vacuum drying, the ball mill is heat-treated at 350-400°C in an airless environment for 8-24h, and then naturally cooled to room temperature to obtain FeSO 4 / CNTs;
[0008] Step 2: According to the molar ratio of Na to Fe being 7:5.5, FeSO 4 / CNTs and anhydrous Na 2 SO 4 The mixture was put into a ball mill, and the mixture was wet-milled at a low speed of 350-450 r / min for 12-24 h under an inert atmosphere, and vacuum-dried in an oven at 40-80 ° C for 6-12 h to obtain a black precursor powder Na 2 SO 4 / FeSO 4 / CNTs;
[0009] Step 3: Prepare the precursor powder Na 2 SO 4 / FeSO 4 / CNTs were compacted tightly under a pressure of 8-12MPa, placed in a tube furnace, and introduced with high-purity argon or nitrogen. The temperature was raised to 350-400℃ at a rate of 1-2℃ / min and kept for 10-24h. The product Na was then cooled to room temperature and ground to obtain a black powder. 7 Fe 5.5 (SO 4 ) 9 / CNTs composites.
[0010] Among them, the mass ratio of iron-based sulfate and dispersed CNTs is 6-78:0.4-6. The lower CNTs content will cause Na 7 Fe 5.5 (SO 4 ) 9 / The electrical conductivity of CNTs decreases and the electrochemical performance deteriorates; higher CNTs will increase costs and cause uneven ball milling, reducing product consistency.
[0011] Among them, the molar ratio of Na to Fe is 7:5.5. The sodium storage electrochemical performance of this molar ratio material is excellent and can provide a higher capacity; the product consistency is high; this Na-Fe ratio composition has not been reported in literature and patents and is a new composition material.
[0012] Among them, step three is to keep warm at 350-400°C for 10-24h. The samples synthesized below 350°C have poor crystallinity, resulting in reduced conductivity and decreased electrochemical performance; above 400°C, some sulfates will decompose to produce impurities; if it is less than 10h, the material reaction is insufficient and the crystallinity deteriorates; if it is more than 24h, the synthesis cost will increase and the synthesis efficiency will be reduced.
[0013] Furthermore, the dispersion treatment is to heat treat the multi-walled carbon nanotubes in a concentrated nitric acid solution at 60-80°C for 12-15h, wash with water until the pH value is 6, and then vacuum dry at 60-80°C for 12-15h.
[0014] Furthermore, the iron-based sulfate is ferrous sulfate heptahydrate, ferrous sulfate monohydrate or anhydrous ferrous sulfate.
[0015] Furthermore, in both step 1 and step 2, zirconia balls are used as ball milling media, and the ball-to-material ratio is set to 10:1 to 20:1.
[0016] Furthermore, anhydrous Na 2 SO 4 The preparation method is as follows: sodium sulfate with or without crystal water is heat-treated in a vacuum oven at 180-220°C for 5-8h to remove surface adsorbed water and / or crystal water, thereby obtaining anhydrous Na 2 SO 4 .
[0017] Furthermore, the inert atmosphere in step 1 and step 2 is argon or nitrogen.
[0018] The second aspect of the present invention is to provide Na prepared by the above-mentioned preparation method 7 Fe 5.5 (SO 4 ) 9 Application of Na / CNTs composites as positive electrode materials for sodium ion batteries. 7 Fe 5.5 (SO 4 ) 9 / CNTs composite material as the positive electrode active material and sodium metal sheet as the negative electrode assembled button battery. 7 Fe 5.5 (SO 4 ) 9 The / CNTs composite material, Ketjen black and polyvinylidene fluoride (PVDF) were mixed into a slurry according to a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added. The mixture was evenly coated on the aluminum current collector in a dry environment and dried in vacuum at 100°C for 12 hours. The electrolyte was 1M sodium perchlorate (NaClO 4 ) was dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 and 5% volume of fluoroethylene carbonate (FEC) was added. The test temperature was room temperature.
[0019] Advantages and beneficial effects of the present invention:
[0020] (1) Na prepared by the method of the present invention 7 Fe 5.5 (SO 4 ) 9 The crystal phase of the CNTs composite material is highly uniform and the morphology is uniform, and the product consistency is good. The synthesis process is highly reproducible, and the Na obtained by changing the iron source, sodium source, and using CNTs with different aspect ratios 7 Fe 5.5 (SO 4 ) 9 Na / CNTs composites 7 Fe 5.5 (SO 4 ) 9 It has high purity, large yield and good controllability, and is easy for large-scale industrial preparation and application in the future.
[0021] (2) Na prepared by the method of the present invention 7 Fe 5.5 (SO 4 ) 9The / CNTs composite material is a sodium-rich composition. This design will not destroy the iron-based sulfate structure even if sodium is provided to the hard carbon negative electrode in the full battery, resulting in sodium loss in the positive electrode, thereby ensuring the overall charge and discharge cycle stability of the battery.
[0022] (3) Na of the present invention 7 Fe 5.5 (SO 4 ) 9 The positive electrode material has good sodium storage capacity, excellent rate performance and stable long cycle life. In addition, compared with layered oxide and vanadium-based polyanion compound positive electrode materials, Na 7 Fe 5.5 (SO 4 ) 9 The positive electrode material has a higher operating voltage (~3.7V) and lower production raw material cost, and has significant advantages in energy density, long cycle performance and production manufacturing cost.
[0023] (4) Na prepared by the method of the present invention 7 Fe 5.5 (SO 4 ) 9 / CNTs composite materials are nano-sized structures, which facilitate rapid ion transport, electron diffusion, and sufficient contact between electrodes and electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The Na prepared in Example 1 7 Fe 5.5 (SO 4 ) 9 X-ray powder diffraction (XRD) pattern of / CNTs composites;
[0025] Figure 2 Na prepared in Comparative Example 1 7 Fe 5.5 (SO 4 ) 9 XRD pattern of the / CNTs composite material, which contains Na 3 Fe(SO 4 ) 3 and FeSO 4 Impurities;
[0026] Figure 3 The Na prepared in Example 1 7 Fe 5.5 (SO 4 ) 9 Infrared spectrum (FTIR) of / CNTs composites;
[0027] Figure 4The Na prepared in Example 1 7 Fe 5.5 (SO 4 ) 9 X-ray photoelectron spectroscopy (XPS) of the / CNTs composite material, a) is the overall spectrum, b) is the fine spectrum of iron (Fe), c) is the fine spectrum of sulfur (S), d) is the fine spectrum of carbon (C);
[0028] Figure 5 The Na prepared in Example 1 and Example 5 7 Fe 5.5 (SO 4 ) 9 Scanning electron microscope (SEM) images of the / CNTs composite material, where a is (Example 1) and b is (Example 5);
[0029] Figure 6 The Na prepared in Example 1 7 Fe 5.5 (SO 4 ) 9 Transmission electron microscopy (TEM) images of the / CNTs composites;
[0030] Figure 7 The Na prepared in Example 1 7 Fe 5.5 (SO 4 ) 9 The constant current charge-discharge curve (GCD) of the first 5 cycles of the CNTs / CNTs composite material as the positive electrode of the sodium ion battery at a current density of 0.1C;
[0031] Figure 8 The Na prepared in Example 1 7 Fe 5.5 (SO 4 ) 9 Rate performance diagram of / CNTs composite material as positive electrode of sodium ion battery at current density of 0.1, 0.2, 0.5, 1.0, 2.0 and 5.0C respectively;
[0032] Fig. 9 The Na prepared in Example 1 7 Fe 5.5 (SO 4 ) 9 Performance diagram of / CNTs composite material as sodium ion battery positive electrode after 700 charge and discharge cycles at 1C current density.
[0033] Fig.10 The Na prepared in Examples 1-5 and Comparative Example 1 7 Fe 5.5 (SO 4 )9 Performance diagram of / CNTs composite material as sodium ion battery positive electrode after 100 charge and discharge cycles at 1C current density. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0035] Example 1
[0036] Dispersing multi-walled carbon nanotubes (CNTs): Heat 0.6 g of multi-walled carbon nanotubes in 30 mL of concentrated nitric acid solution at 70 °C for 12 h, wash with water until the pH is 6, centrifuge or filter, and vacuum dry at 80 °C for 12 h to obtain uniformly dispersed carbon nanotubes (CNTs). The first step is ball milling: 6.501 g of FeSO 4 ·H 2 O and 0.488 g of CNTs were mixed and placed in a 70 mL ball mill. 2 The ball was used as the milling medium, and the ball mass was set to 20 times the total material. 15 mL of acetone was injected, and argon was used as the protective gas at 400 r / min for 12 h. The ball was then vacuum dried at 60 °C for 6 h to obtain black powder FeSO 4 ·H 2 O / CNTs. Then, the black powder FeSO 4 ·H 2 O / CNTs were placed in a tube furnace with argon as carrier gas, heated to 360°C at a rate of 2°C / min and kept for 18 h, then cooled to room temperature to obtain black powder FeSO 4 / CNTs. The second step of ball milling: Take 3.874g of black powder FeSO 4 / CNTs and 2.138g anhydrous Na 2 SO 4 The mixture was placed in a 70 mL ball mill with a ball-to-material ratio of 20:1, 15 mL of acetone was injected, and the mixture was ball milled at 400 r / min for 12 h under argon protection, and then vacuum dried at 60 °C for 8 h to obtain a black powder Na 2 SO 4 / FeSO 4 / CNTs. Tableting: Na 2 SO 4 / FeSO 4 / CNTs powder was manually ground and compacted under 10MPa pressure. One-step pyrolysis: the compacted Na 2 SO 4 / FeSO 4 / CNTs were placed in a tubular furnace with argon as carrier gas, heated to 400℃ at a rate of 2℃ / min and kept at this temperature for 12h, cooled to room temperature, and ground to obtain the final black powder product Na 7 Fe 5.5 (SO 4 ) 9 / CNTs.
[0037] from Figure 1 It can be seen that the Na synthesized by this method 7 Fe 5.5 (SO 4 ) 9 / CNTs are pure phase.
[0038] from Figure 4 It can be seen that the main elements of the sample include Na, Fe, S, O and C, which are different from Na 7 Fe 5.5 (SO 4 ) 9 / CNT phase conforms to; Na 7 Fe 5.5 (SO 4 ) 9 A small part of Fe on the surface of CNTs is oxidized, but the main 2+ and SO 4 2- The C signal exists in large quantities in the form of CC chemical bonds, indicating that CNTs exist in large quantities on the surface of the material.
[0039] from Figure 5 It can be seen that Na 7 Fe 5.5 (SO 4 ) 9 / CNT products have uniform dispersion of CNTs and Na 7 Fe 5.5 (SO 4 ) 9 Exist in the form of nano-sized particles.
[0040] from Figure 6 It can be seen that the Na synthesized by this method 7 Fe 5.5 (SO 4 ) 9 / CNT has good crystallinity and obvious lattice fringes.
[0041] Electrochemical performance test:
[0042] Will Na 7 Fe 5.5 (SO 4 ) 9 / CNTs composite material as the positive electrode active material and sodium metal sheet as the negative electrode assembled button battery. 7 Fe 5.5 (SO 4 ) 9 The / CNTs composite material, Ketjen black and polyvinylidene fluoride (PVDF) were mixed into a slurry according to a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added. The mixture was evenly coated on the aluminum current collector in a dry environment and dried in vacuum at 100°C for 12 hours. The electrolyte was 1M sodium perchlorate (NaClO 4 ) was dissolved in ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 and 5% volume of fluoroethylene carbonate (FEC) was added. The test temperature was room temperature.
[0043] from Figure 7 It can be seen that Na 7 Fe 5.5 (SO 4 ) 9 / The average operating voltage of CNT products is as high as 3.7V, and the cycle stability is good.
[0044] from Figure 8 It can be seen that Na 7 Fe 5.5 (SO 4 ) 9 / CNT products have excellent rate performance, and can still maintain 80mAh g at a high current of 5C -1 The above reversible specific capacity.
[0045] from Fig. 9 It can be seen that Na 7 Fe 5.5 (SO 4 ) 9 The / CNT sample has excellent cycling performance, with a capacity retention rate of 88% after 700 cycles.
[0046] Example 2
[0047] Dispersing multi-walled carbon nanotubes (CNTs): Heat 1.2 g of multi-walled carbon nanotubes in 50 mL of concentrated nitric acid solution at 70 °C for 12 h, wash with water until the pH is 6, centrifuge or filter, and vacuum dry at 80 °C for 12 h to obtain uniformly dispersed carbon nanotubes (CNTs). 4 ·H 2 O and 0.976 g of CNTs were mixed into a 100 mL ball mill. 2The ball was used as the milling medium, and the ball mass was set to 12 times the total material. 21 mL of acetone was injected, and argon was used as the protective gas at 400 r / min for 18 h. The ball was then vacuum dried at 80 °C for 6 h to obtain black powder FeSO 4 ·H 2 O / CNTs. Then, the black powder FeSO 4 ·H 2 O / CNTs were placed in a tube furnace with argon as carrier gas, heated to 380°C at a rate of 2°C / min and kept for 15 h, then cooled to room temperature to obtain black powder FeSO 4 / CNTs. The second step of ball milling: Take 7.748g of black powder FeSO 4 / CNTs and 4.276g anhydrous Na 2 SO 4 The mixture was placed in a 100 mL ball mill with a ball-to-material ratio of 14:1, and 21 mL of acetone was injected. The mixture was ball milled at 400 r / min for 18 h under argon protection and vacuum dried at 80 °C for 8 h to obtain a black powder Na 2 SO 4 / FeSO 4 / CNTs. Tableting: Na 2 SO 4 / FeSO 4 / CNTs powder was ground and compacted under 10MPa pressure. One-step pyrolysis: the compacted Na 2 SO 4 / FeSO 4 / CNTs were placed in a tubular furnace with argon as carrier gas, heated to 400℃ at a rate of 1℃ / min and kept for 12h, cooled to room temperature, and ground to obtain the final black powder product Na 7 Fe 5.5 (SO 4 ) 9 / CNTs.
[0048] Example 3
[0049] Dispersing multi-walled carbon nanotubes (CNTs): Heat 2.4 g of multi-walled carbon nanotubes in 50 mL of concentrated nitric acid solution at 70 °C for 12 h, wash with water until the pH is 6, centrifuge or filter, and vacuum dry at 80 °C for 12 h to obtain uniformly dispersed carbon nanotubes (CNTs). 4 10H 2 O and 1.952 g of CNTs were mixed into a 200 mL ball mill. 2The ball was used as the ball milling medium, and the ball mass was set to 10 times the total material. 45 mL of acetone was injected, and argon was used as the protective gas at 400 r / min for 24 h. The black powder FeSO was collected and dried in a vacuum at 40 °C for 12 h. 4 ·H 2 O / CNTs. Then, the black powder FeSO 4 ·H 2 O / CNTs were placed in a tube furnace with argon as carrier gas, heated to 400°C at a rate of 2°C / min, kept at that temperature for 8 h, and cooled to room temperature to obtain black powder FeSO 4 / CNTs. The second step of ball milling: Take 15.496g of black powder FeSO 4 / CNTs and 8.552g anhydrous Na 2 SO 4 The mixture was placed in a 200 mL ball mill with a ball-to-material ratio of 15:1, and 45 mL of acetone was injected. The mixture was ball milled at 350 r / min for 24 h under argon protection and vacuum dried at 60 °C for 12 h to obtain a black powder Na 2 SO 4 / FeSO 4 / CNTs. Tableting: Na 2 SO 4 / FeSO 4 / CNTs powder was ground and compacted under 10MPa pressure. One-step pyrolysis: the compacted Na 2 SO 4 / FeSO 4 / CNTs were placed in a tubular furnace with argon as carrier gas, heated to 400℃ at a rate of 2℃ / min and kept at that temperature for 24h, cooled to room temperature, and ground to obtain the final black powder product Na 7 Fe 5.5 (SO 4 ) 9 / CNTs.
[0050] Example 4
[0051] Dispersing multi-walled carbon nanotubes (CNTs): Heat 4.29 g of multi-walled carbon nanotubes in 100 mL of concentrated nitric acid solution at 70 °C for 15 h, wash with water until the pH is 6, centrifuge or filter, and vacuum dry at 80 °C for 12 h to obtain uniformly dispersed carbon nanotubes (CNTs). 4 ·H 2 O and 3.49 g of CNTs were mixed into a 500 mL ball mill. 2The ball was used as the milling medium, and the ball mass was set to 20 times the total material. 100 mL of acetone was injected, and argon was used as the protective gas for ball milling at 350 r / min for 24 h. The ball was then vacuum dried at 80 °C for 10 h to obtain black powder FeSO 4 ·H 2 O / CNTs. Then, the black powder FeSO 4 ·H 2 O / CNTs were placed in a tube furnace with argon as carrier gas, heated to 400°C at a rate of 2°C / min and kept for 12 h, then cooled to room temperature to obtain black powder FeSO 4 / CNTs. The second step of ball milling: Take 27.7g of black powder FeSO 4 / CNTs and 15.29g anhydrous Na 2 SO 4 The mixture was placed in a 500 mL ball mill with a ball-to-material ratio of 20:1, 100 mL of acetone was injected, and the mixture was ball milled at 400 r / min for 24 h under argon protection, and then vacuum dried at 80 °C for 10 h to obtain a black powder Na 2 SO 4 / FeSO 4 / CNTs. Tableting: Na 2 SO 4 / FeSO 4 / CNTs powder was ground and compacted under 10MPa pressure. One-step pyrolysis: the compacted Na 2 SO 4 / FeSO 4 / CNTs were placed in a tubular furnace with argon as carrier gas, heated to 400℃ at a rate of 1.5℃ / min and kept at that temperature for 24h, cooled to room temperature, and ground to obtain the final black powder product Na 7 Fe 5.5 (SO 4 ) 9 / CNTs.
[0052] Example 5
[0053] Dispersing multi-walled carbon nanotubes (CNTs): Heat 7.2 g of multi-walled carbon nanotubes in 150 mL of concentrated nitric acid solution at 70 °C for 15 h, wash with water until the pH is 6, centrifuge or filter, and vacuum dry at 80 °C for 15 h to obtain uniformly dispersed carbon nanotubes (CNTs). 4 ·H 2 O and 5.86 g of CNTs were mixed into a 500 mL ball mill. 2The ball was used as the milling medium, and the ball mass was set to 10 times the total material. 100 mL of acetone was injected, and nitrogen was used as the protective gas at 450 r / min for 24 h. The ball was then vacuum dried at 80 °C for 12 h to obtain black powder FeSO 4 ·H 2 O / CNTs. Then, the black powder FeSO 4 ·H 2 O / CNTs were placed in a tube furnace with nitrogen as carrier gas, heated to 400°C at a rate of 2°C / min and kept at that temperature for 24 h, and then cooled to room temperature to obtain black powder FeSO 4 / CNTs. The second step of ball milling: Take 46.49g of black powder FeSO 4 / CNTs and 25.66g anhydrous Na 2 SO 4 The mixture was placed in a 500 mL ball mill with a ball-to-material ratio of 10:1, and 100 mL of acetone was injected. The mixture was ball milled at 450 r / min for 24 h under nitrogen protection, and vacuum dried at 80 °C for 12 h to obtain a black powder Na 2 SO 4 / FeSO 4 / CNTs. Tableting: Na 2 SO 4 / FeSO 4 / CNTs powder was fully ground and compacted under 10MPa pressure. One-step pyrolysis: the compacted Na 2 SO 4 / FeSO 4 / CNTs were placed in a tubular furnace with nitrogen as carrier gas, heated to 400℃ at a rate of 1℃ / min and kept at that temperature for 24h, cooled to room temperature, and ground to obtain the final black powder product Na 7 Fe 5.5 (SO 4 ) 9 / CNTs.
[0054] Comparative Example 1
[0055] Dispersed multi-walled carbon nanotubes (CNTs): 0.6 g of multi-walled carbon nanotubes were heated at 70 °C for 12 h in 30 mL of concentrated nitric acid solution, washed with water until the pH was 6, centrifuged or filtered, and then vacuum dried at 80 °C for 12 h to obtain uniformly dispersed carbon nanotubes (CNTs). 5.81 g of FeSO 4 ·H 2 O was heat treated in a vacuum oven at 200 °C for 12 h to remove crystal water. One-step ball milling: 3.574 g of FeSO 4 and 2.138 g anhydrous Na 2 SO 4The mixture was mixed with 0.3 g of CNTs and placed in a 70 mL ball mill with a ball-to-material ratio of 20:1. 15 mL of acetone was injected and the mixture was ball milled at 400 r / min for 12 h under argon protection and dried in vacuum at 60 °C for 8 h to obtain a black powder Na 2 SO 4 / FeSO 4 / CNTs. Tableting: Na 2 SO 4 / FeSO 4 / CNTs powder was manually ground and compacted under 10MPa pressure. One-step pyrolysis: the compacted Na 2 SO 4 / FeSO 4 / CNTs were placed in a tubular furnace with argon as carrier gas, heated to 400℃ at a rate of 2℃ / min and kept at that temperature for 12h, cooled to room temperature, and ground to obtain the final black powder product Na 7 Fe 5.5 (SO 4 ) 9 / CNTs. Note that the final sample prepared by this one-step ball milling process is not pure phase and contains Na 3 Fe(SO 4 ) 3 and FeSO 4 Impurities.
[0056] from Figure 2 It can be seen that the final sample synthesized after one-step ball milling is not a pure phase, and shows more impurity peaks.
[0057] Fig.10 The Na prepared in Examples 1-5 and Comparative Example 1 7 Fe 5.5 (SO 4 ) 9 Performance diagram of the CNTs / CNTs composite material as a positive electrode for sodium-ion batteries after 100 cycles of charge and discharge at 1C current density. Fig.10 It can be seen that Na 7 Fe 5.5 (SO 4 ) 9 After the production of / CNT is continuously expanded, the product performance remains basically consistent, and the material obtained by the two-step ball milling process is pure phase, which has better performance than the impure phase prepared in Comparative Example 1.
[0058] The Na of the present invention 7 Fe 5.5 (SO 4 ) 9The positive electrode material has a good sodium storage specific capacity. At a rate of 1C, Example 1 is 89.7 mAh / g, Example 2 is 89.2 mAh / g, Example 3 is 88.1 mAh / g, Example 4 is 87 mAh / g, Example 5 is 86.8 mAh / g, and Comparative Example 1 is 71.6 mAh / g.
[0059] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a sodium-enriched sodium iron sulfate composite material, characterized in that: Here are the steps: Step 1, iron-based sulfate and dispersed CNTs are loaded into a ball mill according to a mass ratio of 6-78:0.4-6, and ethanol or acetone solution is injected, and the ball mill is carried out at a low speed of 350-450r / min for 12-24h under the protection of an inert atmosphere, and after vacuum drying, the ball mill is heat-treated at 350-400°C in an airless environment for 8-24h, and the ball mill is naturally cooled to room temperature to obtain FeSO4 / CNTs; Step 2: According to the molar ratio of Na to Fe being 7:5.5, FeSO4 / CNTs and anhydrous Na2SO4 are mixed and put into a ball mill, and the mixture is wet-milled at a low speed of 350-450 r / min for 12-24 h under the protection of an inert atmosphere, and vacuum-dried in an oven at 40-80° C. for 6-12 h to obtain a black precursor powder Na2SO4 / FeSO4 / CNTs; Step 3: The obtained precursor powder Na2SO4 / FeSO4 / CNTs is compacted tightly under a pressure of 8-12 MPa, placed in a tube furnace, and introduced with high-purity argon or nitrogen. The temperature is raised to 350-400°C at a rate of 1-2°C / min and kept at this temperature for 10-24 hours. The powder is then cooled to room temperature and ground to obtain a black powder product Na7Fe 5.5 (SO4)9 / CNTs composite materials.
2. The preparation method according to claim 1, characterized in that: The dispersion treatment is to heat treat the multi-walled carbon nanotubes in a concentrated nitric acid solution at 60-80°C for 12-15h, wash with water until the pH value is 6, and then vacuum dry at 60-80°C for 12-15h.
3. The preparation method according to claim 1, characterized in that: The iron-based sulfate is ferrous sulfate heptahydrate, ferrous sulfate monohydrate or anhydrous ferrous sulfate.
4. The preparation method according to claim 1, characterized in that: In both step 1 and step 2, zirconia balls are used as ball milling media, and the ball-to-material ratio is set to 10:1 to 20:
1.
5. Na7Fe prepared by the preparation method according to any one of claims 1 to 4 5.5 Application of (SO4)9 / CNTs composites as positive electrode materials for sodium ion batteries.
6. The use according to claim 5, characterized in that: Na7Fe 5.5 (SO4)9 / CNTs composite material is used as positive electrode active material, sodium metal sheet is used as negative electrode, and the electrolyte is 1M sodium perchlorate dissolved in ethylene carbonate and diethyl carbonate with a volume ratio of 1:1 and 5% volume of fluoroethylene carbonate added.
7. Na7Fe prepared by the preparation method according to any one of claims 1 to 4 5.5 Application of (SO4)9 / CNTs composites as sodium storage materials.
Citation Information
Patent Citations
Sodium-ion battery composite positive electrode material and preparation method thereof
CN114267838A
Sodium ferric sulfate composite positive electrode material and preparation method and application thereof
CN117457899A
Sodium ferrous sulfate / carbon composite positive electrode material, preparation method and application of sodium ferrous sulfate / carbon composite positive electrode material in sodium ion battery
CN117832453A
Pure-phase sodium ferric sulfate composite positive electrode material and application of sodium ion battery
CN118412445A
Carbon-coated sodium ferric sulfate positive electrode material, preparation method thereof and battery
CN118507681A
Cited By
High-energy-density sodium-ion battery sodium-rich positive electrode material and preparation method and application thereof
CN120319789A
Sodium ferrous sulfate positive electrode material and preparation method thereof
CN121494070A
Ferrous sulfate sodium positive electrode material and preparation method thereof
CN121494070B